Genetic determinants of susceptibility and severity in nonalcoholic fatty liver disease. (April 2011) - Daly, Ann K; Ballestri, Stefano; Carulli, Lucia; Loria, Paola; Day, Christopher P
Nonalcoholic fatty liver disease (NAFLD) in most patients involves only simple hepatic steatosis; however, a minority develop progressive steatohepatitis. Family studies and inter-ethnic differences in susceptibility suggest that genetic factors may be important risk determinants for progressive disease. Polymorphisms in genes affecting lipid metabolism, cytokines, fibrotic mediators and oxidative stress may be associated with steatohepatitis and/or fibrosis, but most of these findings require replication. A recent finding that a nonsynonymous polymorphism in the PNPLA3 gene predicts the extent of steatosis in NAFLD has been replicated in at least eight studies, with several studies also demonstrating an association with fibrosis. A new genome-wide association study has identified several additional novel associations with NAFLD severity. Other disease genes may be identified by similar approaches in the future.